(untitled) (Materiali di Estetica. Terza serie, 2019)
Gillo Dorfles’s thoughts regarding the changes of urban sounds may be defined as farsighted. As shown by his observations and numerous works, Dorfles had already detected the connection between music and noise when he was young and started talking about it when noise pollution was indeed a topic for research, but it was unthinkable that music could be part of it.